(untitled) (Medical Forum Monthly, 2024)
Objective: This study was conducted to evaluate the complication rate of treatment of mandible fracture using 2.0-mm miniplate and MMF for up to two weeks. Study Design: Descriptive study. Place and Duration of Study: This study was conducted at Liaquat University of Medical and Health Sciences Jamshoro, Hyderabad Sindh from May 2004 to April 2006. Patients and Methods: Fifty patients with single mandibular fracture were evaluated in this study at Liaquat University of Medical and Health Sciences Jamshoro, Hyderabad Sindh. Single miniplate was applied according to champy’s principle of osteosynthesis and secured with four mono cortical screws and Maxillomandibular fixation was applied for up to two weeks. Follow up was done for at least eight weeks after surgery. The incidence of infection, malocclusion, delayed union, non union, nerve damage and TMJ dysfunction were evaluated. Results: Bone union was achieved in all patients. No evidence of malocclusion, delayed union, nonunion, nerve damage and TMJ dysfunction observed. Two cases (4%) developed post operative infection and was healed with in 7 to 10 days after administration of antibiotics and local wound care. Conclusion: Single miniplate along with Maxillomandibular fixation for up to two weeks has proven to be the most effective treatment modality for mandible fracture.